Effect of Testicular Boost in Children With Leukemia Receiving Total Body Irradiation and Stem Cell Transplant: A Single-Institution Experience - Erik S. Blomain, MD, PhD; Alice Jiang, BA; Sarah S. Donaldson, MD; Rajni Agarwal, MD; Alice Bertaina, MD, PhD; David Shyr, MD; Michael L. Eisenberg, MD; Richard T. Hoppe, MD; Susan M. Hiniker, MD; Justin Oh, MD (Advances in Radiation Oncology, 2023)
ABSTRACT: Purpose: Children with leukemia who receive fractionated total body irradiation (fTBI) with 12 to 13.2 Gy as part of conditioning for hematopoietic stem cell transplant are frequently treated with an additional 4 Gy testicular boost to reduce the risk of testicular relapse. While institutional practices vary, limited data exists regarding whether the 4-Gy testicular boost reduces the risk of relapse and whether it causes toxicity beyond that imparted by TBI. This study compared the survival and endocrine outcomes among the patients who were treated with and without a testicular boost as part of fTBI from 1990 to 2019 at our center. Methods and Materials: We retrospectively reviewed charts of male children with leukemia treated with fTBI as part of a conditioning regimen for stem cell transplant from 1990 to 2019. Reported outcomes included progression-free survival, testicular relapse rate, and overall survival. Gonadal dysfunction and fertility were assessed by comparing the rate of abnormally low testosterone or high luteinizing hormone or follicular stimulating hormone, number of offspring, fertility service use, and abnormal sperm count in the subsequent follow-up period between the testicular boost and nonboost subset. Results: Ninety-three male patients (63 acute lymphoblastic leukemia, 30 acute myeloid leukemia) with a median age of 9 years (range, 1-22) and follow-up of 3.3 years were included. In addition to 12- to 13.2-Gy fTBI, 51 male patients (54%) received a testicular boost to 4 Gy. There was 1 testicular relapse in the boost subset and none in the nonboost subset. Five-year progression-free survival for the boost and nonboost subset was 74% and 66%, respectively (P = .31). On multivariable analysis, boost was not associated with improved relapse-free survival or overall survival. More patients in the boost subset (35 of 51, 69%) had abnormal serum gonadal blood work compared with the nonboost subset (18 of 42, 43%) (P = .03). Conclusions: Omission of testicular boost may be associated with comparable oncologic but improved gonadal endocrine outcomes and should be further studied.